Evaluation of a Dot -ELIZA for the Diagnosis of Human Hydatid Disease - Ali, W.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Fourty  -tow   Libyan     patients  with  hydatidosis,  which  werereferred to by the physician for the detection of hydatid cyst by X - rays, Ultrasound and CT-Scan.  The  infection rate  in  females and males was(69% )and (31% )respectively .The highest rate 69% was in the liver, followed by the lung( 23.8%), the brain (4.8%) and kidney(2.4%).A total of  42 serum  samples were gathered from Libyan patients infected with hydatidosis, 33 serum samples from patients cases with other parasitic diseases than hydatidosis and 30 serum samples from healthy normal controls and were tested by Dot-ELIZA utilizing antigen B from sheep hydatid fluid, dotted onto nitrocellulose filter discs.lJlg of antigen B per dot, ,serum dilution of 1:800, dilution conjugate of 1:1000 and 45 minutes incubation were found optimal.The sensitivity and specificity of the tests were 97.7% and 98.4%, respectively for detection hydatidosis. No false positive reaction was observed when 31 sera from healthy subjects were assayed. One case of cross-reactions was observe as for serum from a teaniasis person.